Genome Structure of the Opportunistic Pathogen Paracoccus yeei (Alphaproteobacteria) and Identification of Putative Virulence Factors - Lasek, Robert; Szuplewska, Magdalena; Mitura, Monika; Decewicz, Przemysław; Chmielowska, Cora; Pawłot, Aleksandra; Sentkowska, Dorota; Czarnecki, Jakub; Bartosik, Dariusz (Frontiers in Microbiology, 2018)
Bacteria of the genus Paracoccus are common components of the microbiomes of many naturally – and anthropogenically-shaped environments. One species, Paracoccus yeei, is unique within the genus because it is associated with opportunistic human infections. Therefore, strains of P. yeei may serve as an interesting model to study the transition from a saprophytic to a pathogenic lifestyle in environmental bacteria. Unfortunately, knowledge concerning the biology, genetics and genomic content of P. yeei is very fragmentary; also the mechanisms of pathogenicity of this bacterium remain unclear. In this study we provide the first insight into the genome composition and metabolic potential of a clinical isolate, P. yeei CCUG 32053. This strain has a multipartite genome (4,632,079 bp) composed of a circular chromosome plus eight extrachromosomal replicons pYEE1–8: 3 chromids and 5 plasmids, with a total size of 1,247,173 bp. The genome has been significantly shaped by the acquisition of genomic islands, prophages (Myoviridae and Siphoviridae phage families) and numerous insertion sequences (ISs) representing seven IS families. Detailed comparative analysis with other complete genomic sequences of Paracoccus spp. (including P. yeei FDAARGOS_252 and TT13, as well as non-pathogenic strains of other species in this genus) enabled us to identify P. yeei species-specific genes and to predict putative determinants of virulence. This is the first attempt to identify pathoadaptive genetic information of P. yeei and to estimate the role of the mobilome in the evolution of pathogenicity in this species.